2013
DOI: 10.1111/jfb.12096
|View full text |Cite
|
Sign up to set email alerts
|

Using remote underwater video to estimate freshwater fish species richness

Abstract: Species richness records from replicated deployments of baited remote underwater video stations (BRUVS) and unbaited remote underwater video stations (UBRUVS) in shallow (<1 m) and deep (>1 m) water were compared with those obtained from using fyke nets, gillnets and beach seines. Maximum species richness (14 species) was achieved through a combination of conventional netting and camera-based techniques. Chanos chanos was the only species not recorded on camera, whereas Lutjanus argentimaculatus, Selenotoca mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Any application of our boat-based UVC methodology to other environments should consider the influence of depth of deployment and habitat complexity on fish detection probability. Ebner and Morgan (2013) found that the camera deployment in shallow, vegetated environments observed different freshwater fishes than cameras deployed in deeper waters, and the influence of baited cameras slightly increased the detection of some species. Future application may also improve by evaluating the time of arrival for a variety of fishes to establish effective deployment times and quantifying behaviours observed among individual fishes to quantify habitat use (e.g.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Any application of our boat-based UVC methodology to other environments should consider the influence of depth of deployment and habitat complexity on fish detection probability. Ebner and Morgan (2013) found that the camera deployment in shallow, vegetated environments observed different freshwater fishes than cameras deployed in deeper waters, and the influence of baited cameras slightly increased the detection of some species. Future application may also improve by evaluating the time of arrival for a variety of fishes to establish effective deployment times and quantifying behaviours observed among individual fishes to quantify habitat use (e.g.…”
Section: Discussionmentioning
confidence: 93%
“…Fish arrival rates and time of MaxN can be different among fish species and can be a predictor variable in fish density estimates influencing the duration of sampling events for many fishes, particularly slow-moving or cryptic species (Priede and Merrett 1998;Cappo et al 2004). Ebner and Morgan (2013) found most freshwater fish species in Australian waterholes were detected within 10 min of underwater camera deployments while Ellender et al (2012) found that two imperilled freshwater fish in African streams were observed within 15-22 min. This supports our assumption that any sampling or behavioural biases within Lepomis spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mini Baited Remote Underwater Video (BRUV) (hereafter referred to as a ‘mini‐BRUV’) system was used to survey for the presence/abundance of E. daemelii within intertidal habitats as well as for the presence of other fish species within the site. The use of BRUV is an established method for studying fish assemblages (Malcolm et al., ; Ebner and Morgan, ); however, the generally large size of the standard BRUV is impractical for use in intertidal habitats. Utilising small high definition GoPro HERO2 underwater video cameras (http://www.gopro.com), a compact mini‐BRUV system was developed that incorporated a 30 cm bait arm with 2 × 2 kg weights to weight the system along with a small mesh bait bag (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Comparisons with established sampling techniques demonstrate that underwater videography provides similar or sometimes higher detection rates provided that visibility in the water is sufficient (Ellender et al. ; Ebner and Morgan ; Ebner et al. ; Branigan et al.…”
mentioning
confidence: 99%